Pendampingan budidaya ayam petelur dengan pakan gamallusforte sebagai upaya pencegahan stunting: Laying hen farm mentoring on the gamilusforte feed to preven stunting - Astuti, Endah P.; Syah, Muhammad E.; Shanti, Elvika F. A.; Sunarsih, Tri; Astuti, Pudji; Sarmin, Sarmin; Astuti, Andriyani; Airin, Claude M. (Fakultas Peternakan Universitas Papua, 2024)
ABSTRACT The poverty rate in Sumberwungu District is still high, namely 1,119 households or 17.59%. This is because the majority of people do not go to school/did not finish elementary school as many as 1,872 people, so they work as farmers, livestock breeders, artisans and agricultural laborers. This Community Service is a very strategic program to support the Sumberwungu District program. The target partner for this community service activity is the Griya Livestock Group, which is a group of breeders in the Sumberwungu District chaired by Tukino with 22 members. This activity was carried out in Sumberwungu District in the Livestock Farming Group which was carried out for 4 months. The method for implementing this service activity begins with socialization, training on livestock management and making animal feed according to Gamallusforte, implementation of Gamallusforte, operational assistance and marketing of chicken livestock products. The activity implementation phase began with program socialization which was carried out on September 20 2021 at the Sumberwungu Village Hall. After socializing the activities, the next activity was implementation of livestock management training with the result that 90% of participants' skills increased regarding how to raise livestock. Egg production continues to increase day by day. Supporting factors that can strengthen the success of community empowerment in the Griya Animal Husbandry Group: training, access to resources, capital and funding, technology and innovation, partnerships, support from related stakeholders, land area, as santri therapy: and providing PMT to wasting and under-five children stunting. Keywords: Farm mentoring; Gamilusforte feed; Laying hen; Stunting ABSTRAK Angka kemiskinan Kalurahan Sumberwungu masih tinggi yaitu sebanyak 1.119 Rumah Tangga atau sebesar 17,59 %. Hal ini disebabkan oleh sebagian besar masyarakat tidak sekolah/ tidak tamat SD sebanyak 1.872 jiwa, sehingga berprofesi sebagai petani, peternak, tukang dan buruh tani. Pengabdian Masyarakat ini merupakan program yang sangat strategis untuk mendukung program RPJMD/RPJM Kalurahan Sumberwungu. Mitra sasaran kegiatan pada pengabdian masyarakat ini yaitu Kelompok Griya Peternakan, merupakan kelompok peternak yang berada di Kalurahan Sumberwungu diketuai oleh Tukino dengan jumlah anggota 22 orang. Kegiatan ini dilaksanakan di Kalurahan Sumberwungu pada kelompok Griya Peternakan yang dilaksanakan selama 4 bulan. Metode pelaksanaan kegiatan pengabdian ini diawali dengan melaksanakan sosialisasi, pelatihan manajemen peternakan dan pembuatan pakan ternak sesuai TTG Gamallusforte, penerapan TTG Gamallusforte, pendampingan operasional dan pemasaran hasil ternak ayam. Tahap pelaksanaan kegiatan diawali dengan sosialisasi program yang dilaksanakan pada tanggal 20 September 2021 bertempat di Balai Kalurahan Sumberwungu. Setelah sosialisasi kegiatan pelaksanaan kegiatan selanjutnya yaitu pelatihan manajemen peternakan dengan hasil 90% keterampilan peserta meningkat terkait cara berternak. Produksi telur terus meningkat dari hari ke hari. Faktor pendukung yang dapat memperkuat keberhasilan pemberdayaan masyarakat pada Kelompok Griya Peternakan: adanya pelatihan, akses terhadap sumber daya, modal dan pendanaan, teknologi dan inovasi, kemitraan, dukungan stakeholder terkait, luas lahan, sebagai terapi santri: dan memberikan PMT pada balita wasting dan stunting. Kata kunci: Ayam petelur; Gamallusforte; Pendampingan; Stunting